2016
DOI: 10.1089/ars.2016.6664
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and Kidney Disease: Role of Oxidative Stress

Abstract: Intrarenal oxidative stress plays a critical role in the initiation and progression of diabetic kidney disease (DKD). Enhanced oxidative stress results from overproduction of reactive oxygen species (ROS) in the context of concomitant, insufficient antioxidant pathways. Renal ROS production in diabetes is predominantly mediated by various NADPH oxidases (NOXs), but a defective antioxidant system as well as mitochondrial dysfunction may also contribute. Recent Advances: Effective agents targeting the source of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
443
0
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 491 publications
(453 citation statements)
references
References 290 publications
(413 reference statements)
2
443
0
8
Order By: Relevance
“…45) Moreover, it has been reported that all forms of acute and chronic renal injuries, regardless of species, is associated with enhanced generation of ROS, 46) which linked ROS to renal damage. Besides, cell senescence also plays a pivotal role in renal damage.…”
Section: Hfd and Hg Culture Comparisonmentioning
confidence: 99%
“…45) Moreover, it has been reported that all forms of acute and chronic renal injuries, regardless of species, is associated with enhanced generation of ROS, 46) which linked ROS to renal damage. Besides, cell senescence also plays a pivotal role in renal damage.…”
Section: Hfd and Hg Culture Comparisonmentioning
confidence: 99%
“…Nox family is one of the major contributors on ROS generation in the kidney [10]. Our previous studies with db/db and STZ-induced mice have implied increases of protein and mRNA levels of renal Nox 1, 2, and 4, which were significantly reduced by APX-115, a panNox inhibitor [17,18].…”
Section: Discussionmentioning
confidence: 95%
“…Accumulation of reactive oxygen species (ROS) leads to renal inflammation and structural changes in the kidney, stimulating the pathological process of DKD [6][7][8]. Among signaling molecules involved in renal ROS generation, NADPH oxidases (Nox) belongs to an enzyme system majorly contributing to the pathophysiology of DKD [9,10]. The kidneys express several Nox isoforms, Nox1, Nox2, Nox4, and Nox5 present in mesangial, podocyte, glomerular endothelial, and tubulointerstitial cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Erythropoietin deficiency is the predominant cause of anemia in kidney diseases (Babitt and Lin, 2012) due to the fact that kidney is the main source of erythropoietin. So also, oxidative stress has been implicated in the genesis and progression of kidney diseases (Jha et al, 2016), long-chain polyunsaturated fatty acids present in the kidney enhance the oxidative stress-induced kidney disease.…”
mentioning
confidence: 99%